Exploring Challenges in Learning Arabic as a Second Language: a Study of Code-Switching and Code-Mixing - Muna, Zulfa Tsalitsatul; Nur Fadhilah, Fina; Eka Rachmawati, Annisa; Setiyawan, Agung (Ta'lim al-'Arabiyyah: Jurnal Pendidikan Bahasa Arab & Kebahasaaraban, 2024)
Code-switching and code-mixing are linguistic phenomena in everyday communication and second language learning. However, this phenomenon can be a challenge for learners in the context of learning Arabic. This research examines code switching and code mixing in Arabic learning at Mumārasah Language Excellence Program of MA Ali Maksum Yogyakarta and the factors that cause code switching and code mixing. This research is field research with a descriptive qualitative approach. The data sources in this research are teachers and students of class ten. Data collection techniques used include observation, interviews, and documentation. Meanwhile, in analyzing the data, researchers used data reduction techniques, data presentation, and conclusions. The results show that in Arabic learning at Mumārasah Program of MA Ali Maksum, there is external code-switching from Arabic to Indonesian and two types of code-mixing: 1) external code-mixing, involving the insertion of English or Arabic words and 2) mixed code-mixing, involving a mix of Indonesian, Arabic, English, and Javanese. This article explores factors contributing to code-switching and code-mixing, such as speaker characteristics, interlocutors, popular language trends, and humor. While these phenomena are well-studied in linguistics and language learning, the article aims to provide strategic advice for Arabic learners. By effectively utilizing code switching and code mixing, learners can enhance communication, overcome barriers, and gain confidence in Arabic.overcome communicative barriers and boost their confidence in Arabic.